Biometry of the mahseer, Tor putitora (Hamilton) collected from Garo Hills, Meghalaya - Gupta, M Das (Indian Journal of Fisheries, 2011)
There is practically no information on the biology of the mahseers from the North- Eastem India, except that of Dasgupta (1989), on the copper mahseer Acrossocheilus hexagonolepis (McClelland). Hence this study was conducted.